Second-Order Slip Effect on MHD Flow and Radiative Heat Transfer through Porous Medium due to an Exponentially Stretching Sheet - Kaushik, Preeti; Mishra, Upendra (Trends in Sciences, 2022)
The magnetohydrodynamic (MHD) boundary layer flow and radiative heat transfer with second-order slip condition are investigated in this paper. The fluid flow is considered towards an exponentially stretching sheet. The effect of magnetic field and thermal conductivity are taken into account. The obtained nonlinear mathematical expression of the flow are transformed into ordinary differential equations by similarity transformation. The coupled higher order nonlinear ordinary differential equations are solved numerically. The solution for velocity and temperature profile against the first and second-order slip parameters are analyzed. Significant changes are observed in skin friction coefficient and Local Nusselt number due to the magnetic parameter. The characteristics of the flow are discussed through graphs for different pertinent parameters. The results designate that the Local Nusselt number reduces with the increased value of magnetic parameter but opposite behavior is observed for the skin friction coefficient. The rate of heat transfer decreases with higher value of Prandtl number and enhances for Radiation parameter. HIGHLIGHTS Phenomenon of an exponentially stretching sheet with thermal conductivity also incorporate in fluid flow Behavior of magnetic parameter (M) and Radiation parameter (R) are analyzed Highly nonlinear mathematical equations are solved numerically Variation of velocity profile obtained for the first and second order slip parameters GRAPHICAL ABSTRACT